Effects of vitamin E and selenium on thyroid status, adrenocorticotropin hormone, and blood serum metabolite and mineral concentrations of Japanese quails reared under heat stress (34°C) - Gursu, MF; Sahin, N; Kucuk, O (Wiley-Liss, 2003)
This study was conducted to determine the effects of vitamin E and selenium (Se) on triiodothyronine (T-3), thyroxine (T-4), thyroid stimulating hormone (TSH), adrenocorticotropin hormone (ACTH), and serum glucose, urea, triglyceride, cholesterol, Ca, P. Na, and K concentrations of Japanese quails reared under heat stress (34degreesC). One-hundred twenty 10-day-old Japanese quails were randomly assigned to four treatment groups with three replicates of 10 birds each. The birds with a 2 x 2 factorial design received either two levels of vitamin E (125 and 250 mg/kg of diet) or two levels of selenium (0.1 and 0.2 mg/kg of diet). Greater dietary vitamin E and selenium inclusions resulted in a greater (P = 0.00 1) serum T-3, T-4, and TSH, but lower (P = 0.001) ACTH concentrations. No interactions between vitamin E and selenium were detected (P greater than or equal to 0.11) for serum concentrations of T-3, T-4, TSH, and ACTH. Serum glucose, urea, triglyceride, and cholesterol concentrations decreased (P = 0.001), whereas protein concentrations increased (P = 0.001) when both dietary vitamin E and selenium increased. Serum albumin concentrations increased (P = 0.001) with greater dietary vitamin E but did not change with dietary selenium (P = 0.16). No interactions on any blood metabolites were detected (P greater than or equal to 0.11). Serum activities of serum glutamic oxalate transaminase and serum glutamic pyruvate transaminase were not influenced by dietary vitamin E or selenium (P greater than or equal to 0.42). However, serum activity of alkaline phosphatase increased (P = 0.001) with both increasing dietary vitamin E and selenium. There were no interactions detected for the serum enzyme activities (P greater than or equal to 0.09). Increasing both dietary vitamin E and selenium caused an increase in serum concentrations of Ca, P, and K (P = 0.001), but a decrease in serum concentrations of Na (P = 0.001). No interactions were detected for serum mineral concentrations (P greater than or equal to 0.07) except for P (P = 0.001). Results of the present study showed that dietary vitamin E and selenium have synergistic effects, and that supplementing a combination of dietary vitamin E (250 mg) and selenium (0.2 mg) positively influences some blood parameters that may positively influence the performance of Japanese quails under heat stress.
Keywords: Japanese quails; heat stress; vitamin E; selenium; thyroid; serum metabolites